Parental socioeconomic position and midlife allostatic load: a study of potential mediators - Christensen, Dinne S. (BMC Public Health, 2018)
BACKGROUND: The mechanisms underlying the association of parental socioeconomic position with later life allostatic load remain unclear. The present study aims to examine potential pathways underlying this association: personality, social relations, intelligence and education. METHODS: The study comprised 361 members of the Copenhagen Perinatal Cohort who participated in two subsequent follow-ups: the Prenatal Development Project (mean age 27 years) and the Copenhagen Aging and Midlife Biobank study (mean age 50 years). Allostatic load was based on 14 biomarkers representing the inflammatory, metabolic and cardiovascular system measured at midlife. Information on potential mediators was collected in young adulthood, and their role in the association of parental socioeconomic position with midlife allostatic load were examined in linear regression path analyses. RESULTS: Parental socioeconomic position at one year was inversely associated with midlife allostatic load (β = − 0.238, p < .001). No mediation effects were found for personality or social relations. In a model including intelligence and education, a significant indirect effect was found for education (β = − 0.151, p < .001). A significant direct effect remained (β = − 0.111, p = .040). CONCLUSIONS: Parental socioeconomic position was inversely associated with allostatic load in midlife. Results suggest that part of this association was mediated by education. A better understanding of the non-cognitive pathways related to education is an important prerequisite for the development of effective intervention strategies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-018-5956-x) contains supplementary material, which is available to authorized users.